2005
DOI: 10.1364/opex.13.004869
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of nonlinear phase shifts with third-order dispersion in short-pulse fiber amplifiers

Abstract: We show that nonlinear phase shifts and third-order dispersion can compensate each other in short-pulse fiber amplifiers. This compen-sation can be exploited in any implementation of chirped-pulse amplification, with stretching and compression accomplished with diffraction gratings, single-mode fiber, microstructure fiber, fiber Bragg gratings, etc. In particular, we consider chirped-pulse fiber amplifiers at wavelengths for which the fiber dispersion is normal. The nonlinear phase shift accumulated in the amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 11 publications
2
56
0
Order By: Relevance
“…Optimum levels of nonlinearity was also observed to balance or compensate other physical process such as GVD, third order dispersion (TOD) and gain filtering in fiber lasers [6,7]. Generally one can say the nonlinear property of fibers make it a seminal platform for fundamental research as well as interesting applications that could not be provided with other optical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Optimum levels of nonlinearity was also observed to balance or compensate other physical process such as GVD, third order dispersion (TOD) and gain filtering in fiber lasers [6,7]. Generally one can say the nonlinear property of fibers make it a seminal platform for fundamental research as well as interesting applications that could not be provided with other optical systems.…”
Section: Introductionmentioning
confidence: 99%
“…The TOD compensation is possible to implement with the help of nonlinearity [4,5]. In [4], it was shown that nonlinear phase shift and TOD can compensate each other in short-pulse fiber amplifiers.…”
Section: Introductionmentioning
confidence: 99%
“…In [4], it was shown that nonlinear phase shift and TOD can compensate each other in short-pulse fiber amplifiers. The nonlinear phase shift accumulated in the amplifier can be compensated by the TOD of the combination of a fiber stretcher and grating compressor.…”
Section: Introductionmentioning
confidence: 99%
“…The CPA technique (Diels & Rudolph, 2006;Maine et al, 1988;Mourou et al, 1998) consists in generating ultrashort pulses with nanojoules of energy in a main oscillator laser, then temporally stretching these pulses by chirping its frequency (dispersion control) (Rullière, 1998) to decrease its power and intensity, allowing its amplification up to more than a million times without damaging the amplification chain components; after the amplification, the pulses are compressed to durations close to their original ones and directed to the applications. When the CPA technique became prominent, the pulses stretching and compression were mainly done with diffraction gratings (Fork et al, 1984;Martinez, 1987a;Martinez, 1987b;Treacy, 1969), although nowadays other techniques are disseminated, such as the use of Chirped Mirrors (Nisoli et al, 1997;Szipocs et al, 1994), fiber stretchers (Zhou et al, 2005) and prisms and grisms compressors (Chauhan et al, 2010). As the years went by, scientific and technological developments led to the dissemination of ultrashort pulses systems based in other mode-locking schemes such as SESAMs (Semiconductor Saturable Absorber Mirrors) (Keller, 2010) and gain media including chromium, ytterbium and neodymium doped crystals (Diels & Rudolph, 2006), neodymium doped glasses (Badziak et al, 1997), erbium doped fibers (Krauss et al, 2010), Optical Parametric CPAs (OPCPA) (Dubietis et al, 2006) and picosecond semiconductor lasers (Koda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%